2013
DOI: 10.1002/pbc.24898
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of self‐reported physical activity in children and adolescents before and during cancer treatment

Abstract: Due to the well known importance of physical activity during childhood and the identified risk of inactivity during cancer treatment, supervised exercise interventions should be implemented into acute treatment phase to enhance activity levels and ensure a continuously support by qualified exercise professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 23 publications
2
55
0
12
Order By: Relevance
“…In summary, we demonstrated that well-known side effects of pediatric cancer and medical treatment as well as inactivity [14,36,39] may lead to highly diminished coordination, flexibility, speed, and strength at the end of the acute treatment phase. Between 50 and 91 % of the study participants achieved motor performance scores below their age-and gender-matched normative data.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In summary, we demonstrated that well-known side effects of pediatric cancer and medical treatment as well as inactivity [14,36,39] may lead to highly diminished coordination, flexibility, speed, and strength at the end of the acute treatment phase. Between 50 and 91 % of the study participants achieved motor performance scores below their age-and gender-matched normative data.…”
Section: Discussionmentioning
confidence: 95%
“…Bone tumor patients showed a more pronounced decline in all motor abilities (except handgrip strength) than leukemia patients, which might be due to orthopedic restrictions and surgery or to the well-documented reduction of physical activity levels [14,39]. Specific physical therapy, adapted to individual performance limitations, is essential for this patient group, as well as a general promotion of enjoyable exercises to maintain adequate activity levels and physical fitness [40].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…What is more, they observed that cancer also contributed to limiting children's mobility and increased the time spent in a sitting position [11]. Additionally, the study conducted by Götte et al [12] also proved that children undergoing cancer treatment presented a significantly lower level of physical activity in all dimensions of everyday Fisher's test p-value < 0,05 life. The weekly amount of time devoted to exercises diminished considerably.…”
Section: Discussionmentioning
confidence: 83%
“…The most substantial decrease in physical activity during treatment has been observed in patients with bone cancer and those treated in stationary conditions. owing to the well-known benefits of physical activity during childhood and a proven risk of physical inactivity during cancer treatment, supervised exercise interventions should be implemented during therapy [12]. The research by Anzar et al…”
Section: Discussionmentioning
confidence: 99%